The safety and efficacy of radiofrequency ablation following endoscopic submucosal dissection for Barrett's neoplasia. Issue 3 (2nd December 2017) - Subramaniam, S; Kandiah, K; Chedgy, F; Meredith, P; Longcroft-Wheaton, G; Bhandari, P
SUMMARY: The current standard of treating early Barrett's neoplasia is resection of visible lesions using endoscopic mucosal resection (EMR) followed by ablative therapy to the Barrett's segment. There is increasing evidence to support the use of endoscopic submucosal dissection (ESD) where en-bloc resection and lower recurrence rates may be achieved. However, ESD is associated with deep submucosal dissection when compared to EMR. This may increase the risk of complications including stricture formation with subsequent radiofrequency ablation (RFA) therapy. The aim of this study is to compare the safety and efficacy of RFA following EMR and ESD as well as when RFA was used without prior endoscopic resection. The primary outcome measure was complication rates. Clearance of dysplasia (CRD) and clearance of intestinal metaplasia (CRIM) were secondary outcomes. A retrospective analysis of a cohort of 91 patients referred for RFA from a single academic tertiary center was performed. The choice of endoscopic resection method was tailored according to the lesion type and morphology. Focal and circumferential ablation was performed after initial follow up endoscopy postresection. Patients proceeded straight to RFA in the absence of any visible lesions. In this study, the ESD group had a higher proportion of cancers compared to the EMR cohort (74.1% vs. 30.2%, P < 0.01) prior to RFA. All complications post RFA occurred in the groups with previous endoscopic resection. There was no significant difference in the total complication rate (7.4% vs. 9.3%, P = 0.78) and stricture formation rate (3.7% vs. 9.3%, P = 0.38) between the ESD and EMR groups. CRD was achieved in 96.3% in the ESD group, 88.4% in the EMR group, and all patients in the RFA alone group. CRIM rates were similar in the EMR and ESD groups (81.4% vs. 85.2%) but higher in the RFA alone group (90.5%). In conclusion, RFA following ESD is very effective and not associated with an increased risk of complications compared to EMR. This supports the application of RFA in the treatment algorithm of patients undergoing ESD for Barrett's neoplasia.